Biological management of bacterial leaf spot of mungbean caused by Xanthomonas axonopodis pv. vignaeradiatae - and J.P. VERMA, P. K. BORAH*, J.K. JINDAL (Indian Phytopathology, 2002)
As many as 110 bacterial cultures were established from mung bean (Vigna radiata) phylloplane showing distinct colour and colony characters. A bacteriophage was isolated from the Xanthomonas axonopodis pv. vignaeradiatae (Xav) infected mung bean plants also. Antagonistic nature of these phylloplane bacteria (Plb) and phage (XMP-1) against the bacterial leaf spot pathogen were tested in vitro. Five isolates were found antagonistic, exhibiting inhibition zones ranging from 6 to 25 mm. The most promising antagonistic phylloplane bacterium (Plb-2) was identified as a strain of Bacillus sp. Effectiveness of Plb-2 and XMP-1 as biocontrol agents in the suppression of Xav from seed, seed coat and cotyledon of mung bean was assessed. The pathogen was effectively eliminated from mung bean seeds when these were dipped in a mixture of Xav and Plb at 1:1 ratio. The phage multiplied in mung bean seeds in presence of Xav, but it failed to eliminate Xav completely from seed, seed coat and cotyledons even at 1:60(Xav:phage) concentration. Maximum reduction in susceptible reaction was observed when Plb was pre-inoculated 24 h prior to challenge inoculation of Xav at 1:2. No protection was obtained when Xav was challenged by Plb at all concentrations tested. Thephage was also effective in providing protection when challenge inoculation (24 h) was done with Xav. Application of the phage reduced the Xav population in plants to levels insufficient to induce susceptible reaction. Increased population of Plb (4.5 x106 from 5.5 x 103 cfu/cm2) in challenge inoculation by Xav or vice versa (4.5 x 106 from 6.0 x 104 cfu/cm2) were recorded, which suggested that Plb could multiply in presence of Xav in mung bean leaves. Seed treatment with Plb at 2:1 ratio (Xav:Plb) andwith phage at 1:60 (Xav:phage) ratio were effective in stimulating germination and restricting seedling infection to 10.0 and 15.9%, respectively, as compared to 68% in control. The results indicated that Plb and phage strains ant.